Equitable Research Partnerships in Public Health - Maqsood, Fiza (My University, 2023)
This integrated learning experience report is an extensive review of my enriching internship experience at Feed the Future Innovation Lab for Livestock Systems located at the University of Florida, Gainesville, Florida. This experience bolstered my practical skills in data analysis, international research collaborations, and program evaluation, allowing me to integrate MPH academic knowledge with real-world scenarios. Collaborating with a dynamic team of public health professionals, I actively contributed to initiatives addressing equity in global research collaborations. I extended nutrition and food safety assistance to ongoing research projects under Innovation Lab for Livestock Systems. I collected the data and analyzed it using statistical software to inspect in-country authorship inclusion from lower-income and middle- income country partners. Later, I presented the results at the Innovation Lab for Livestock Systems faculty meeting in the form of a presentation. To assist with the ongoing Innovation Lab for Livestock Systems projects I scheduled interviews with the principal investigators of projects and my preceptor to optimize research implementation considering nutrition outcomes. I generated an SPSS code sheet for continuous monitoring of authorships, a white paper addressing authorship inclusion from low-resource countries, a presentation, a post-interview follow-up sheet to improve the current Innovation Lab for Livestock Systems projects, and a research bibliography on Water, Sanitation, and Hygiene (WaSH). As I embark on my public health career, I am confident that the insights gained from these experiences will serve as a solid foundation, guiding my future endeavors in promoting health equity and well-being for communities.
Keywords: Research Equity; Global Research Collaborations; Food Safety; Nutrition Outcomes; Water, Sanitation and Hygiene (WaSH)